Airway mechanics, gas exchange, and blood flow in a nonlinear model of the normal human lung - Liu, C H; Niranjan, S C; Clark, Jr, J W; San, K Y; Zwischenberger, J B; Bidani, A (Journal of applied physiology (1985), 1998)
A model integrating airway/lung mechanics, pulmonary blood flow, and gas exchange for a normal human subject executing the forced vital capacity (FVC) maneuver is presented. It requires as input the intrapleural pressure measured during the maneuver. Selected model-generated output variables are compared against measured data (flow at the mouth, change in lung volume, and expired O2 and CO2 concentrations at the mouth). A nonlinear parameter-estimation algorithm is employed to vary selected sensitive model parameters to obtain reasonable least squares fits to the data. This study indicates that 1) all three components of the respiratory model are necessary to characterize the FVC maneuver; 2) changes in pulmonary blood flow rate are associated with changes in alveolar and intrapleural pressures and affect gas exchange and the time course of expired gas concentrations; and 3) a collapsible midairway segment must be included to match airflow during a forced expiration. Model simulations suggest that the resistances to airflow offered by the collapsible segment and the small airways are significant throughout forced expiration; their combined effect is needed to adequately match the inspiratory and expiratory flow-volume loops. Despite the limitations of this lumped single-compartment model, a remarkable agreement with airflow and expired gas concentration measurements is obtained for normal subjects. Furthermore, the model provides insight into the important dynamic interactions between ventilation and perfusion during the FVC maneuver.